OPTIMALISASI IRIGASI SPRINKLER UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium cepa L.) - Krismiratsih, Fitri; Fibriani, Suwinda; Khomsatun Ni'mah (Fakultas Pertanian Universitas Janabadra, 2025)
Water is an important component in shallot cultivation activities, optimal water availability is very necessary in shallot cultivation activities, especially in the early stages of growth and bulb formation. Traditional irrigation methods tend to be wasteful and unpublished in air distribution which can result in decreased yields, especially in cultivation activities carried out in areas with limited air. Sprinkler irrigation appears as a potential solution to optimize air distribution through a spraying mechanism that allows for more even air distribution. The research design used was a one-factorial Completely Randomized Design with five replications. Irrigation carried out in this study was in the form of traditional control 100% manual irrigation needs (I0), sprinkler 75% manual irrigation volume (I1), sprinkler 100% manual irrigation volume (I2), sprinkler 150% manual irrigation volume (I3) and sprinkler 200% manual irrigation volume (I4) which were given once in the morning at 06.00 -07.00. This study aims to analyze the effect of the use of a sprinkler irrigation system on shallot productivity. The results showed that sprinkler irrigation with a volume of 200% of the manual method gave the best results on plant height, number of tillers, dry weight of the stump, and diameter of the shallot bulb. In contrast, the traditional irrigation method with 100% manual volume produced the lowest bulb weight loss. Sprinkler application with 200% manual irrigation volume can significantly increase shallot production.